2014
DOI: 10.1111/dme.12452
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and pharmacological interventions for depression in patients with diabetes mellitus: an abridged Cochrane review

Abstract: Psychological and pharmacological interventions positively affect depression outcomes in patients with diabetes at the end of treatment. Furthermore, short-term glycaemic control improved moderately in pharmacological trials. Most outcomes have not been investigated sufficiently. Moreover, there is a lack of follow-up data for pharmacological trials limiting the evidence on the sustainability of treatment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 57 publications
(112 reference statements)
3
87
0
5
Order By: Relevance
“…The authors concluded that both psychological and pharmacological interventions had a moderate but clinically significant effect on depression outcomes in people with diabetes. They also found that glycaemic control improved moderately in pharmacological trials, but the evidence was inconclusive for the impact of psychological interventions on blood glucose regulation [17]. An important limitation of this systematic review is that glycaemic control was often not the main outcome of the trials that were included.…”
Section: How To Treat Depression In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that both psychological and pharmacological interventions had a moderate but clinically significant effect on depression outcomes in people with diabetes. They also found that glycaemic control improved moderately in pharmacological trials, but the evidence was inconclusive for the impact of psychological interventions on blood glucose regulation [17]. An important limitation of this systematic review is that glycaemic control was often not the main outcome of the trials that were included.…”
Section: How To Treat Depression In Diabetesmentioning
confidence: 99%
“…Baumeister et al conducted a systematic review and meta-analysis of 19 randomised controlled trials, aiming to determine the effects of psychological and pharmacological interventions for depression in patients with diabetes and depression [17]. The primary outcomes were depression and glycaemic control.…”
Section: How To Treat Depression In Diabetesmentioning
confidence: 99%
“…Some studies show that reducing depressive symptoms by antidepressants in patients with DM is associated not only with better health behaviour, but also with favourable outcomes in glycaemic control 61,62 . Although limited, there is evidence on the safety of antidepressants as related to glycaemic control, but when selecting an antidepressant clinicians should consider present diabetic complications and major side effects of different antidepressant groups 63 . A general recommendation for adult patients is to use fluoxetine or sertraline for depression in DM suffering patients 64 .…”
Section: Medicationmentioning
confidence: 99%
“…There are only two studies that support psychological interventions as a treatment for subthreshold depression in people with diabetes [25] carried out an abridged Cochrane review to summarize and critically evaluate the effectiveness of psychological and pharmacological interventions for depression in patients with both diabetes and depression. Six randomized controlled trials investigated the effects of psychological interventions in depression, but only one specified that they included minor depression [26].…”
Section: Managing Subthreshold Depressionmentioning
confidence: 99%